Adsorption-desorption of glyphosate in tropical sandy soil exposed to burning or applied with agricultural waste - Garba, Jamilu; Abd Wahid, Samsuri; Ahmad Hamdanı, Muhammad Saıful; Faruq Sadiq, Tariq (Murat Yakar, 2024)
The present study investigated glyphosate adsorption-desorption in Malaysian sandy soil exposed to burning or applied with cow dung or rice husk ash (RHA). One gram each of the adsorbents (control, burnt soil, soil + cow dung, soil + RHA) was separately and in replicate mixed with solution of 20 mL of glyphosate at different initial concentrations (0, 25, 50, 100, 150, 200, 250 and 300 mg L-1), shaken for 24 hours, centrifuged at 10, 000 rpm for 10 minutes and later the decanted supernatants were collected. Desorption study follow immediately through addition of 20 mL of 0.01 M CaCl2 solution and then treated like adsorption study. Glyphosate analysis was done using high performance liquid chromatography with fluorescence detector and isotherm data was fitted to linear, Freundlich, Langmuir and Temkin models. Freundlich best fits the adsorption of glyphosate and application of cow dung or RHA enhanced the soil affinity for glyphosate. Freundlich isotherm constant (KF) for soils treated with RHA and cow dung were 9.768 mg g-1 and 6. 751 mg g-1, respectively as compared to 3.189 mg g-1 for the control soil. However, the greatest KF value (387.238 mg g-1) was recorded by burnt Benta soil. Glyphosate adsorption by both control and treated soils was favourable (0.044 < RL < 0.3). This study suggests that adsorption occurred through physical processes involving diffusion, complexation or ligand exchange. Glyphosate desorption from soils treated with cow dung and RHA was either hysteretic or reversible. Burning this soil should be discouraged due to its effect on increasing glyphosate mobility and possible groundwater contamination. Meanwhile, agricultural waste can be applied to this soil even though it might lead to an increased glyphosate mobility but because of its potential positive effect on the soil's biological functions, the glyphosate ions are bound to be degraded.